Person-Environment Fit on Organizational Citizenship Behaviour and Employee Engagement Among Administrative Staff of Public Universities in Accra, Ghana - Aryee, Esther Maame Efua; Asumeng, Maxwell; Agyemang, Collins Badu (Journal of Organizational Psychology, 2024)
This study aimed to assess the impact of person-environment fit on work-related outcomes among administrative staff of public universities in Accra. A sample of 300 administrative staff was selected from public universities in the Greater Accra Region to partake in the study using the purposive and snowball sampling method. The study discovered a positive significant relationship between employees fit and work-related outcomes as well as an interaction between two dimensions of engagement (intellectual and affective) and organizational citizenship behavior. The study's findings also reveal that various factor such as tenure and age positively impacted the employee’s performance of organizational citizenship behavior and engagement levels.